Pollination, pollen tube growth, and fertilization independently contribute to fruit set and development in tomato - Tran, Long T.; Sugimoto, Koichi; Kasozi, Michael; Mitalo, Oscar W.; Ezura, Hiroshi (Frontiers in Plant Science, 2023)
In flowering plants, pollination, pollen tube growth, and fertilization are regarded as the first hierarchical processes of producing offspring. However, their independent contributions to fruit set and development remain unclear. In this study, we examined the effect of three different types of pollen, intact pollen (IP), soft X-ray-treated pollen (XP) and dead pollen (DP), on pollen tube growth, fruit development and gene expression in “Micro-Tom” tomato. Normal germination and pollen tube growth were observed in flowers pollinated with IP; pollen tubes started to penetrate the ovary at 9 h after pollination, and full penetration was achieved after 24 h (IP24h), resulting in ~94% fruit set. At earlier time points (3 and 6 h after pollination; IP3h and IP6h, respectively), pollen tubes were still in the style, and no fruit set was observed. Flowers pollinated with XP followed by style removal after 24 h (XP24h) also demonstrated regular pollen tubes and produced parthenocarpic fruits with ~78% fruit set. As expected, DP could not germinate and failed to activate fruit formation. Histological analysis of the ovary at 2 days after anthesis (DAA) revealed that IP and XP comparably increased cell layers and cell size; however, mature fruits derived from XP were significantly smaller than those derived from IP. Furthermore, there was a high correlation between seed number and fruit size in fruit derived from IP, illustrating the crucial role of fertilization in the latter stages of fruit development. RNA-Seq analysis was carried out in ovaries derived from IP6h, IP24h, XP24h and DP24h in comparison with emasculated and unpollinated ovaries (E) at 2 DAA. The results revealed that 65 genes were differentially expressed (DE) in IP6h ovaries; these genes were closely associated with cell cycle dormancy release pathways. Conversely, 5062 and 4383 DE genes were obtained in IP24h and XP24h ovaries, respectively; top enriched terms were mostly associated with cell division and expansion in addition to the ‘plant hormone signal transduction’ pathway. These findings indicate that full penetration of pollen tubes can initiate fruit set and development independently of fertilization, most likely by activating the expression of genes regulating cell division and expansion.